Theme cities for health: are they the superior Healthy Cities?. (30th September 2020) - De Leeuw, E; Forbat, J; Simos, J
Abstract: Since the early 1980s we have witnessed a proliferation of 'Theme Cities' with the WHO 'Healthy Cities' networks a very early adopter, together with local government initiatives that focused on environmental health and sustainability. These days such networks range very broadly, from Citta Slow and Child-Friendly Cities to sustainable, resilient, festival, happy, garden, winter, safe, inclusive and many more theme-centered international networks of local governments and communities. We undertook a political analysis of the extent to which these networks formally recognise and address the drivers of inequity in societies around the world, and to which extent they are ready to act truly glocally. We found that 'Sustainable Cities' rank highly, with WHO/EURO and PAHO style 'Healthy Cities' a close second. 'Transition Towns and Communities' are in a category of their own and can be considered a potentially important political voice for glocal health equity. Key messages: Healthy Cities are Theme Cities - but not all do well to promote health equity. Sustainability and health (as per the SDGs) have enormous glocal health potential.